Research on alkali metal-modified Pd catalyst for oxygen removal from propylene - Zhao, Jinchong; Jiang, Jie; Wen, Song; Zhang, Jing; Zhang, Changsheng; Sheng, Nan; Liang, Wei; Sun, Bing; Xu, Wei; Yang, Zhe; Pan, Yuan (Frontiers in Chemistry, 2022)
Graphical Abstract To recycle the propylene safely from a gas mixture consisting of propylene and oxygen, alkali metal-modified Pd catalysts were used to remove oxygen from the gas with the help of hydrogen.